Implementation of Psychology of Islamic Development of Students at SD Khoiru Ummah West Bogor - Mayang Trisna Wardani; Nesia Andriana; Imas Kania Rahman (Universitas Muhammadiyah Enrekang, 2024)
This research aims to identify specifically the implementation of Islamic developmental psychology for students at Khoiru Ummah Elementary School, West Bogor. In this research, researchers used a descriptive qualitative approach. The data collection technique was carried out analytically in an inductive manner in detail according to observation data, interviews with related parties, and valid written data. The psychological aspects of Islamic development discussed include physical, cognitive and emotional development. The results of this research show that the implementation of Islamic developmental psychology is implemented at Khoiru Ummah Elementary School, West Bogor through learning activities at school and at home. Islamic teachings are the basis for building student learning activities at school and home.